2015
DOI: 10.1016/j.nutres.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 polyunsaturated fatty acids revert renal responses induced by a combination of 2 protocols that increase the amounts of advanced glycation end product in rats

Abstract: Renal dysfunction is a severe complication that is caused by diabetes mellitus. Many factors associate the progression of this complication with high levels of proinflammatory and pro-oxidant substances, such as advanced glycation end products (AGEs), which form a heterogeneous group of compounds that can accumulate in tissues such as retinas, joints, and kidneys. The hypothesis of this study is that n-3 polyunsaturated fatty acids (n-3 PUFAs) have a nephroprotective effect on rats after exposing them to a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Also PUFA have been associated with anti‐inflammatory effects . Indeed, a recent study observed that dietary supplementation of n‐3 PUFA appears to prevent renal dysfunction on diabetic rats after exposing them to high levels of AGE, via antioxidant and anti‐inflammatory pathways . Our data suggest that both low‐fat diets (LFHCC and LFHCC n‐3) provide a healthy effect on MetS patients compared to HSFA diet, but show an intermediate effect regarding to AGE content, compared to the HMUFA diet.…”
Section: Discussionmentioning
confidence: 56%
“…Also PUFA have been associated with anti‐inflammatory effects . Indeed, a recent study observed that dietary supplementation of n‐3 PUFA appears to prevent renal dysfunction on diabetic rats after exposing them to high levels of AGE, via antioxidant and anti‐inflammatory pathways . Our data suggest that both low‐fat diets (LFHCC and LFHCC n‐3) provide a healthy effect on MetS patients compared to HSFA diet, but show an intermediate effect regarding to AGE content, compared to the HMUFA diet.…”
Section: Discussionmentioning
confidence: 56%
“…The renal protective effect for n-3 PUFAs is inconsistency among the diet manipulation studies. Many epidemiologic and animal studies show the correlation of n-3 PUFAs deficiency and CKD progression151617181920. And PUFAs may interfere with renal fibrogenesis via inhibiting pro-inflammatory cytokine production as well as renin and nitric oxide (NO) systems21.…”
mentioning
confidence: 99%
“…The optimal dosage regimen for intraperitoneally administered alloxan is a single high dose between 150 and 200 mg/kg (Federiuk et al, 2004; de Assis et al, 2015). Although most rats developed type-1 DM after administration of alloxan, a few rats developed type-2 DM, characterized by stable high blood glucose values, with normal ketone concentration (Federiuk et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins (20 μg) were separated by SDS-PAGE on 10% (w/v) acrylamide and 0.275% (w/v) bisacrylamide gels and then electrotransferred onto nitrocellulose membranes according to (de Assis et al, 2015). Membranes were incubated for 12 h with the appropriate primary antibody (MCT1, 1:800; MCT2, 1:600; Pierre et al, 2000) and β-tubulin, 1:2000 (Santa Cruz Biotechnology, Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%